1974
DOI: 10.1021/bi00710a013
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the mannan from Saccharomyces strain FH4C, a mutant constitutive for invertase biosynthesis. I. Significance of phosphate to the structure and refractoriness of the molecule

Abstract: The cell wall mannan from Saccharomyces strain FH4C (a yeast mutant which forms large amounts of the mannan-enzyme, invertase) was examined. The mannan can be fractionated into neutral and acidic components on DEAEcellulose. Covalently bound phosphate is responsible for the acidic properties of the polysaccharide. Gel filtration studies indicate that the mannan has a molecular weight range from 40,000 to >300,000 daltons. The susceptibility of FH4C mannans to a bacterial a-mannosidase was inversely related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The growth and harvesting of Saccharomyces mutant FH4C, and the preparation of Arthrobacter -mannosidase, FH4C bulk mannan, its neutral and acidic components, and mannan core have been described (Colonna and Lampen, 1974).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth and harvesting of Saccharomyces mutant FH4C, and the preparation of Arthrobacter -mannosidase, FH4C bulk mannan, its neutral and acidic components, and mannan core have been described (Colonna and Lampen, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…Alkali mannan core was prepared by the procedure used for making bulk mannan core (Colonna and Lampen, 1974). A yield of 334 mg of alkali mannan core was obtained by exhaustive enzymolysis of alkali mannan (0.82 g) with 3.8 units of a-mannosidase.…”
Section: Methodsmentioning
confidence: 99%
“…The glycoprotein of Saccharomyces cerevisiae X 2180 has a mannose/phosphate ratio of 38:1 and contains phosphorodiester bridges linking 3-O-a-D-mannopyranosyl-a-D-mannopyranose (1-6) to a threeunit side chain of the mannan portion of the molecule (14) (756). The phosphate groups that occur in phosphaterich fractions of S. cerevisiae cell walls shield mannosyl residues from attack by a-D-mannosidase (188). The phosphate groups that occur in phosphaterich fractions of S. cerevisiae cell walls shield mannosyl residues from attack by a-D-mannosidase (188).…”
Section: Phosphonomannansmentioning
confidence: 99%
“…Treatment of the phosphorylated glycopeptides with ot-mannosidase released mannose, but phosphorylated hexose was not liberated. In this regard, Colonna and Lampen [21] have reported that phosphomannose residues are not suitable substrates for tx-mannosidase.…”
Section: Resultsmentioning
confidence: 99%